The Semantical Analysis of “Boka” Custom Wedding In Buton - Andi Mulyani Kone; Chuzaimah Chuzaimah; Fatmalasari Fatmalasari (Tamaddun Life, 2016)
This research is to explain analysis "boka" in the marriage system Buton tribe. The objectives of this study are to describe the process of boka and the meaning of boka in wedding. This research is to describe the processes of boka in wedding traditions in Buton and to explain the meaning of boka in wedding traditions in Buton. The method used in this research is the semantic the analysis. The purpose of these methods to identify meaning boka in Buton tribe. Explaining in accordance with the function, meaning and implementation in Buton society. That the of Boka wedding tradition in Buton and the meaning of Boka wedding tradition in Buton. The results of the study showed meaning boka a massive amount to be incurred by any person in carrying out activities related to the customs of communities Buton. Boka also means an object or exchange.